A Research concept paper multiple case study on the performance-related need of home-based garment manufacturing micro-enterprises in the National Capital Region (NCR) - David, Joanna Rizza A. (College of Home Economics, University of the Philippines Diliman, 2020)
The micro-enterprise sector continues to generate millions of jobs for Filipinos. Their contribution to the national economy is valuable, yet, reports show cases of exploitation and meager working conditions (Lazo, 1992). In the garments and textiles industry, home-based micro-enterprise are usually at the bottom-most of the supply chain. Most of the micro-enterprises in the industry are limited to subcontracting for medium to large companies which result to very minimal profit. This research concept paper proposes a methodology on identifying and analyzing the performance-related needs of home-based garment manufacturing micro-enterprises in the National Capital Region (NCR). Addressing these needs is not only beneficial to the enterprise but also to the industry as a whole. Additionally, this could contribute the govenrment's Micro, Small, and Medium Enterprises (MSME) development plan. Other literary works discussed in this research concept work revolve arount the history of the Philippine garments industry, the concepts of homeworking, subcontracting, resource management and garment manufacturing, and studies on job satisfaction. A qualitative comparison of the micro-enterprise's "Current Performance" and "Ideal Performance" shall serve as the conceptual framework of the multiple case study. This is anchored from scholarly claims about how job satisfaction is a function between "what is obtained" and "what is wanted". The job satisfaction results, in terms to human, physical, and organizational resources, shall be used as the parameters to determine the performance-related needs of the micro-enterprise. Lastly, a proposed methodology with instrument shall be laid out for future reference. This includes recommendations on data gathering and possible themes for data presentation and data analysis.